2018
DOI: 10.9734/ajsspn/2018/42631
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Different Sources of Potassium on the Nutrient Status of Saline Calcareous Soil and Carrot (Daucus carota L.) Yield and Quality

Abstract: Aims: A field experiment was performed in a saline calcareous soil. Its aim was to evaluate the fertilization effects of potassium (K) from different sources in the form of a liquid solution sprayed on both plant and soil on some soil properties and on the carrot (Daucus carota L.) yield and quality. The purpose of the study is to try replacing the traditional soil application of some K fertilizers by spraying application using the liquid solution form.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
1
1
0
Order By: Relevance
“…These results are in accordance with Zewail et al, (2011) on faba bean and Salim et al (2014) on potato. Also, the vegetative growth and storage roots traits of carrot were significantly increased by K foliar applications (El-Abou El-Nasr and Ibrahim, 2011; Omar and Ramadan, 2018;Shaban et al, 2018). Respecting the positive effect of K foliar application in the present study may be due to that potassium maintenance the cell membrane stability, osmotic regulation, root elongation and dry mass .…”
Section: The Vegetative Growth and Storage Roots Yieldsupporting
confidence: 53%
See 1 more Smart Citation
“…These results are in accordance with Zewail et al, (2011) on faba bean and Salim et al (2014) on potato. Also, the vegetative growth and storage roots traits of carrot were significantly increased by K foliar applications (El-Abou El-Nasr and Ibrahim, 2011; Omar and Ramadan, 2018;Shaban et al, 2018). Respecting the positive effect of K foliar application in the present study may be due to that potassium maintenance the cell membrane stability, osmotic regulation, root elongation and dry mass .…”
Section: The Vegetative Growth and Storage Roots Yieldsupporting
confidence: 53%
“…Moreover, K controls many physiological and biochemical processes reflexed on crops growth, yield and quality (Wang and Wu, 2013;Hasanuzzaman et al, 2018). Consequently, many authors suggested that using K sources as foliar application enhanced the vegetative growth, yield and the biochemical composition of fodder beet Kassab et al (2012), potato Salim et al (2014), onion Behairy et al (2015 and carrot by (Abou El-Nasr and Ibrahim 2011; Omar and Ramadan 2018; Shaban et al 2018).…”
Section: Introductionmentioning
confidence: 99%